Penerapan Standar Pelayanan PT. ASDP Indonesia Terhadap Calon Penumpang Berdasarkan Peraturan Menteri Perhubungan Nomor 37 Tahun 2015 di Pelabuhan Ferry Waijarang Kabupaten Lembata - Marianus Leopoldo Due Hipir; Yohanes G. Tuba Helan; Agustinus Mahur (Hakim, 2023)
The purpose of this research is to analyze the application of PT ASDP Indonesia's service standards to prospective passengers based on the Minister of Transportation Regulation Number 37 of 2015 concerning sea transportation passenger service standards at the Waijarang Ferry port, Lembata Regency. This research is empirical legal research using a descriptive qualitative approach. The types of data used are Primary and Secondary Data. Using data processing techniques are interviews and literature studies. The results showed that: (1) The standard of passenger service eligibility at the Waijarang Ferry Port terminal is generally very good but there are still certain parts that need to be improved such as infrastructure, including: There is no evacuation route, still using a manual check-in system, information on ship arrivals and departures still using papa announcements, unavailability of waiting rooms, the waiting room is very dirty and even looks if it is very neglected, there is no special room for smokers and a special room for nursing mothers, there is still a lack of lighting such as: there is only 1 spotlight and it is not enough to illuminate the port terminal, this is an obstacle for both officers and passengers to move up / down the ship. (2) Factors inhibiting the implementation of service standards at the waijarang ferry port terminal are the lack of infrastructure facilities at the waijarang ferry port terminal and the lack of budget experienced by the Lembata Regency Government and PT.ASDP Indonesia Ferry in Lembata.